ANALISIS POPULASI NEPENTHES SPP DI HUTAN RAWA GAMBUT, KALAMPANGAN, KALIMANTAN TENGAH - Mansur, Muhammad (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Population analysis of Nepenthes spp in peat swamp forest was conducted atKalampangan, Central Kalimantan on November-December 2007. This place includeÃ‚Â to part of one million hectare area of peat land project in 1996 which are planed toÃ‚Â convert agricultural land. Peat swamp forest is one of commonly Nepenthes habitatÃ‚Â at Kalampangan. One plot (50 x 100 m) was establihed for population analysis study.Ã‚Â We found 230 individu from three species, that is; Nepenthes ampullaria, N. rafflesianaÃ‚Â and N. gracilis. In study site, N. ampullaria is dominant species with Important ValueÃ‚Â (IV) is 120,43% and then followed by N. gracilis (IV= 97,30%) and N. rafflesiana (IV=Ã‚Â 82,27%).Key Words : Population analysis, Nepenthes, peat swamp forest, Kalampangan,